The question of metalaxyl resistance on late blight causing pathogen Phytophthora infestans in Estonia - Runno-Paurson, Eve; Koppel, Mati (MTT, 2007)
Metalaxyl containing fungicides are commonly used by Estonian potato growers because of their efficiency in control of potato late blight. Metalaxyl-resistant isolates have become an important part of Estonian population of Phytophtora infestans. The aim of current study was to measure the frequency of metalaxyl resistance among Estonian population of Phytophtora infestans and to test efficacy of metalaxyl based fungicides in control of potato late blight. 138 isolates of Phytophtora infestans were collected from conventional, experimental and small scale growers fields in different parts of Estonia in 2003-2005 and assessed for resistance to metalaxyl. Metalaxyl resistant, intermediate and sensitive isolates were recorded at frequency of 37.1, 45.4 and 15.1%, respectively. Statistically significant differences (P<0.001) between locations, potato growing field types and years in the frequency of resistance to metalaxyl were observed. The proportion of metalaxyl-resistant isolates from different locations ranged from 0 to 67%. Metalaxyl resistant isolates were predominant (66.7%) on conventional potato fields in 2004 and 2005 where metalaxyl consisting fungicide had been applied. In 2004 none metalaxyl-resistant strains were detected among isolates collected from the field (Naha) where metalaxyl containing fungicide was not used. As might be expected, insensitivity was more often found at conventional fields, where metalaxyl was commonly applied, than small scale growers fields where fungicides were rarely used. The increase of frequency of metalaxyl-resistant isolates has been detected in period from 2003 to 2005. Even the proportion of metalaxylresistant isolates fluctuates from year to year there are strong evidences that quantity of metalaxyl-resistant isolates has been increased compared with previous results (Runno, et al. 2005). Reason for such increase could be the more consistent use of metalaxyl containing fungicides. Metalaxyl showed lowered efficacy only in conditions of extreme late blight pressure in 2004. Therefore metalaxyl could be effectively used for control of potato late blight in maximum of two times during the growing period. As long as metalaxyl is used according to the recommendations in Estonia it is unlikely that metalaxyl-resistant isolates will completely displace sensitive isolates. Several reports suggest that resistance is unstable in the population and is selected anew each year, increasing steadily during the season and declining over winter (Gisi & Cohen 1996). Trials of late blight control with metalaxyl containing fungicide Ridomil Gold MZ 68 WG were performed in the same period. Metalaxyl containing fungicide was applied 2 times in all three years. The foliage of untreated plots was completely destroyed for the end of the growing season in all trial years. Metalaxyl provided high protection in 2003 and 2005, but showed lowered efficacy only in conditions of extreme late blight pressure in 2004 when the foliage was infected during the period when metalaxyl was used. The trial result show that in spite of occurrence of resistant strains the use of metalaxyl consisted fungicides is still effective. Therefore metalaxyl could be used effectively for control of potato late blight in maximum of two times in beginning of the fungicide treatments. By following the application rules for metalaxyl fungicides it is possible to restrict the development of metalaxyl-resistant strains and thus avoid the reduction of efficacy of the fungicide.
Keywords: Ka